ҚАРАҚАЛПАҚ ХАЛЫҚ ПЕДАГОГИКАСЫНДА БАЛАЛАРДЫҢ ОЙЛАЎЫН ЖЕТИЛИСТИРИЎДЕ ЖУМБАҚЛАРДЫҢ ӘҲМИЙЕТИ - Ибрагимова, Л.А. (FAN va JAMIYAT, 2021)
The article examines the role of riddles in the development of logical thinking of children in the Karakalpak folk pedagogy and the role of riddles in the development of thinking, curiosity and inventiveness of young generation.